2023
DOI: 10.1002/tea.21884
|View full text |Cite
|
Sign up to set email alerts
|

Belonging in science classrooms: Investigating its relation to students' contributions and influence in knowledge building

Abstract: Meaningful participation in science and engineering practices requires that students make their thinking visible to others and build on one another's ideas. But sharing ideas with others in small groups and classrooms carries social risk, particularly for students from nondominant groups and communities. In this paper, we explore how students' perceptions of classrooms shape their contributions to classroom knowledge building in science across a wide range of classrooms. We examine the claim that when students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Studies have shown that underrepresented students of color felt pressured to conform to a standard of whiteness to achieve, or be perceived to achieve, academic success (Mills, 2020). Increasing peer support, as this project sought to do, and fostering a culture that values the different perspectives and assets the students bring to their learning may mitigate the aforementioned pressure to conform, increase a true sense of belongingness and contribute to knowledge-making (Meador, 2018;Nivet, 2011;Penuel et al, 2024;Rodriguez, 2015).…”
Section: Harnessing Values and Beliefsmentioning
confidence: 99%
“…Studies have shown that underrepresented students of color felt pressured to conform to a standard of whiteness to achieve, or be perceived to achieve, academic success (Mills, 2020). Increasing peer support, as this project sought to do, and fostering a culture that values the different perspectives and assets the students bring to their learning may mitigate the aforementioned pressure to conform, increase a true sense of belongingness and contribute to knowledge-making (Meador, 2018;Nivet, 2011;Penuel et al, 2024;Rodriguez, 2015).…”
Section: Harnessing Values and Beliefsmentioning
confidence: 99%